HOUSE OF BLACK SOLDIER FLIES PETERNAKAN DAN GALERI EKOSISTEM LALAT TENTARA HITAM - Mikael Morgan; Alvin Hadiwono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The Bantar Gebang Integrated Waste Disposal Site (Bantar Gebang Landfill) is the largest landfill in Asia. This unique ecosystem is born from millions of garbage which include mountains of inorganic and organic waste, thousands of scavengers, and millions of flies. However, the ecosystem in this landfill has not worked well, the components in the ecosystem still work independently and do not work in mutualism way. The program is present with the aim of maximizing the existing ecosystem in this landfill, by making the components as one unit. Such as the Black Soldier flies breeding program which is made from organic waste, a waste workshop for the scavengers, and an information gallery about flies and garbage for the outside people. Processing organic waste naturally (using Black Soldier flies), make this program is very environmentally and ecologically friendly. Design methods such as sustainability and biomimicry are used to produce projects that care about the environment, and target the psychological level of the people. By doing so, the project is expected to be able to help overcome the problem of organic waste in the Bantar Gebang Landfill, as well as open up public knowledge about waste management. Keywords: Bantar Gebang Landfill; disposal; flies, scavengers; waste.AbstrakTempat Pembuangan Sampah Terpadu (TPST) Bantar Gebang merupakan TPST terbesar se-Asia. Ekosistem yang unik lahir dari jutaan sampah yang meliputi gunungan sampah organik anorganik, ribuan pemulung, serta jutaan lalat. Akan tetapi, ekosistem di TPST ini belum bekerja dengan baik, antar komponen dalam ekosistem masih bekerja sendiri-sendiri dan tidak bekerja secara mutualisme. Program hadir dalam tujuan memaksimalkan ekosistem yang ada di TPST ini, dengan menjadikan antar komponen sebagai satu kesatuan. Seperti program peternakan lalat BSF yang berbahan dasar sampah organik, workshop sampah bagi para pemulung, dan galeri informasi mengenai lalat dan sampah bagi masyarakat luar. Mengolah sampah organik secara alami (menggunakan lalat BSF), maka program ini menjadi sangat ramah lingkungan dan ekologis. Metode perancangan seperti keberlanjutan dan biomimikri dipakai untuk menghasilkan proyek yang peduli terhadap lingkungan, serta menargetkan pada tingkat psikologis masyarakat. Dengan begitu, proyek diharapkan dapat membantu mengatasi masalah sampah organik di TPST Bantar Gebang, serta membuka wawasan masyarakat luas tentang pengolahan sampah.